Hubungan antara Nilai Sistem Poin Kegiatan Kemahasiswaan dengan Kemampuan Manajemen Waktu Mahasiswa Pendidikan Dokter Universitas Sebelas Maret Surakarta - Ikhsan Marsaid; Suyatmi FK UNS; Murkati FK UNS (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Student activity point system is a measurement system for student activities which is obtained when student participates in a non-academic activity. Student activity is also a founding way and a supervision method towards student activities in Sebelas Maret University. This research aims to determine the relationship between students time management skills with the achievement of student activities point system. Methods: Research design in this study using an observational analytic design with the type of cross-sectional study. The sample was the entire medical student class of 2011 who meet the criteria numbered 179 students. Data collection for time management questionnaire was taken in November 2014 using Time Management Self Assessment questionnaire from Fleet & Raume while the data of student activities point system was taken from Medical Student Executive Board of University of Sebelas Maret Surakarta. The data processed with Kolmogorov Smirnov and Spearmans rho test using a Statistical Product and Service Solution (SPSS) 17.00 for Windows software. Results:. The result of spearmans rho correlation test showed the value of correlation coefficient is -0.001 and p-value 0.985. Conclusions: student activity point system and the ability of time management did not have a significant relationship Keywords: SPKK, time management, student activity, student activity unit